Imaging Mismatch of Nail in the Eyeball: What’s next? Poster Presentation - Case Report - Resident - Christella Caroline; Gladys Kusumowidagdo; Burhana Mawarasti; Michael Hartono; Julie Dewi Barliana; Rio Rhendy; Yunia Irawati; Ari Djatikusumo (Majalah Oftalmologi Indonesia, 2023)
Introduction : A retained foreign body (FB) can lead to severe complications, the most devastating of which is eye loss. We present a discrepancy of imaging that resulted in a dilemma in the approach management of a mixed global-adnexal FB case. Case Illustration : A 31-year-old man came to the emergency room with blurry vision for 1.5 hours after a nail hit his right eye (RE). The visual acuity of RE is light perception. Ophthalmological examination revealed a central Y-shaped full-thickness corneal laceration with iris and vitreous prolapse. The lens appeared cloudy, and the posterior segment was difficult to assess. Imaging showed a foreign metal object asa nail in the oculi to intraconal without penetration to the orbital wall. He was planned to undergo FB extraction with corneal laceration repair and aspiration of lens mass irrigation. However, the nail was hard to find intraoperatively because the vitreous and choroid kept coming out. Hence evisceration with DFG was performed. The nail was found more posteriorly and attached to the bone. Discussion : While primary repair is the standard practice for open globe injury, managing retained intraocular metallic foreign bodies is controversial. Imaging such as CT scans can help determine the location of FB and approach management. In this case, imaging showed the FB was in the iris plane and not penetrating the orbital wall, so primary repair and FB extraction were planned. Conclusion : The imaging may not always be accurate in determining the exact location of FB, and the surgical approach may need to be adjusted accordingly.